The relationship between tooth decay with stress and BMI among elementary students in Iran - Hosseinpour, Fatemeh; Panahi, Rahman; Omidi, Baharan Ranjbar; Khorasani, Erfan; Dehghankar, Leila (Frontiers in Public Health, 2022)
Background Tooth decay is one of the most common chronic diseases among children worldwide. Stress and body mass index are also amongst the arguable risk factors which will affect people considerably. They include biological (hormones and blood sugar), socio-economic, and environmental factors and also lifestyle. In the present study, the relationship between tooth decay with stress and BMI in children was therefore investigated. Materials and methods This was a cross-sectional study of a descriptive-analytical type. A total of 350 students who were referred to the clinic of the faculty of dentistry at Qazvin University of Medical Sciences during 2021–2022 were selected through convenience sampling method to participate in the study. First, the students underwent a dental examination after being measured on their height and weight. Then, two questionnaires; namely, demographic information and Children's Stress Symptom Scale (CSSS) of Scherer and Ryan-Wenger were completed by the children's parents through self-reporting. The collected data were analyzed using SPSS software version 23 and then descriptive statistics and logistic regression were applied. Results The mean BMI of the participating students was in the normal range. The prevalence of tooth decay among participants was 76.9% (269 people). The mean and standard deviation of stress scores was 6.85 ± 4.01 out of 26, which was at a low level. Also, the mean and standard deviation of the BMI were 22.78 ± 5.28, which was within the normal range. The results of the logistic regression showed that the variables of “father's level of education,” “family's economic status,” “the experience of the toothache during the past year,” “the oral health status,” “the frequency of tooth brushing,” “flossing,” “stress,” and “BMI” were influential factors in tooth decay (P <0.05). Conclusion Students who had improper BMI, more stress, less educated fathers, families with poor economic status, the experience of toothache within the past year, poor oral health status, and those who used toothbrushes and floss to a minimal degree suffered more tooth decay. Therefore, it is necessary that we pay more attention to these students in designing and implementing educational programs to prevent tooth decay.